Left ventricular forces distribution in patients with heart failure and reduced ejection fraction. (4th February 2022) - Monosilio, S; Filomena, D; Sannino, M; Birtolo, IL; Cimino, S; Tonti, G; Pedrizzetti, G; Benedetti, G; Fedele, F; Maestrini, V; Agati, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Hemodynamic forces (HDFs) are the forces exchanged between the blood and the myocardium. Estimation of their magnitude and alignment could be a novel marker of cardiac dysfunction. Purpose: To describe left ventricular (LV) HDFs values and distribution in patients with heart failure with reduced ejection fraction (HFrEF) and to compare them with those of a group of healthy controls. Methods: A cohort of 26 non-ischemic patients with an initial diagnosis of HFrEF was enrolled. All of them underwent basal 2D echocardiography evaluation.  Off-line HDFs estimation using a dedicated software based on speckle-tracking echocardiography was conducted. HDFs were normalized for the LV volume and expressed as a percentage of the force of gravity. HDFs were assessed over the entire cardiac cycle, in systole and diastole, both in apex to base (A-B) and latero-septal (L-S) directions. The distribution of LV HDFs was evaluated by L-S over A-B HDFs ratio (L-S/A-B HDFs ratio). HDFs of HFrEF patients were compared with those of 24 healthy volunteers. Results: HFrEF patients showed smaller values of A-B HDFs during the entire cardiac cycle (5, 2 ± 1, 24% vs 12, 3 ± 3, 6%; p = 0, 001), in systole (7, 2 ± 2% vs 16, 6 ± 6, 3%; p = 0, 001) and diastole (3, 3 ± 0, 8% vs 7, 1 ± 3, 6%; p = 0, 001). Moreover, comparing HFrEF subjects with healthy volunteers, the former had lower L-S HDFs during the entire cardiac cycle (1, 6 ± 0, 4% vs 2 ± 0, 7%; p= 0, 022) and in systole (1, 6 ± 0, 5% vs 2, 3 ± 0, 8%; p = 0, 003), while in diastole they showed inappropriate high values of L-S HDFs (1, 7 ± 0, 6% vs 1, 8 ± 0, 9%; p = 0, 999). Consequently, HFrEF patients had higher  values of L-S/A-B ratio during the entire cardiac cycle (32 ± 6, 9 vs 15 ± 7, 7; p = 0, 001), in systole (23, 5 ± 7, 4 vs 14, 7± 4, 2; p = 0, 001), but particularly in diastole (52 ± 10, 8 vs 28 ± 13, 6; p = 0, 001), showing an important HDFs misalignment. Conclusion: When compared with healthy controls, HFrEF patients presented intraventricular fluid alterations characterized by lower HDFs magnitude and a significant HDFs misalignment, especially in diastole. Further studies are needed to confirm these initial results and to assess the effects of therapy on these new parameters.